Using Decision Aids to Improve Auditors' Conditional Probability Judgments. - Bonner, Sarah E.; Libby, Robert (The Accounting Review, 1996)
Examines the effectiveness of two types of decision aids designed to alleviate the effects of one type of task-knowledge mismatch on auditors' judgments. Organization of audit planning tasks; Content and organization of auditors' knowledge; Specific processing problems caused by mismatch between task organization and knowledge organization.